2015
DOI: 10.2141/jpsa.0140109
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Egg-related Traits in the Onagadori (Japanese Extremely Long Tail) Breed of Chickens

Abstract: The Tosa-no-Onagadori (briefly Onagadori) is one of the native Japanese chickens that is characterized by extremely long tail feathers in males, and thus designated as a "Special National Natural Treasure" of Japan. We investigated the timing of sexual maturity of the Onagadori and White Leghorn hens and the quality of the first 10 eggs laid by these young hens to obtain basic information for reproducing the Onagadori efficiently and also to assess their usefulness as research material for quantitative trait l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Since Nagoya and Yakido breeds are used for mating to produce Jidori commercial chickens, their eggs are continuously available in the Livestock Research Institute. Previous works revealed that hens from the other Japanese fancy breeds, Oh-Shamo and Onagadori, produce some differences in egg characteristics in comparison with White Leghorn ( Goto et al., 2015 ; Goto and Tsudzuki, 2017 ). Therefore, Japanese indigenous chickens will have a potential to express distinct feature of egg traits.…”
Section: Introductionmentioning
confidence: 99%
“…Since Nagoya and Yakido breeds are used for mating to produce Jidori commercial chickens, their eggs are continuously available in the Livestock Research Institute. Previous works revealed that hens from the other Japanese fancy breeds, Oh-Shamo and Onagadori, produce some differences in egg characteristics in comparison with White Leghorn ( Goto et al., 2015 ; Goto and Tsudzuki, 2017 ). Therefore, Japanese indigenous chickens will have a potential to express distinct feature of egg traits.…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of chickens have extreme phenotypic characteristics such as body size, feathers, growth, eggs, meat, and behavior. For example, the Japanese indigenous chicken breeds of "Onagadori" has extremely long tail feathers in male [3,4], while the weight of male "Oh-Shamo" reaches 4-6 kg [3,5,6]. Thus, the indigenous chickens have a large potential for studying genetic and phenotypic diversity [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significant breed effects were found on eggshell colors (lightness, redness, and yellowness), with RIR hens laying darker brown eggs than AUS hens. White to brown variation in eggshell color is a heritable quantitative trait [9,10,11], and eggshell colors of Oh-Shamo, White Leghorn, Hy-line Brown, and Onagadori chickens were reported [33,34,35]. Comparing this study to previous work, eggs appear to decrease in color from brown to white in the order of Hy-Line Brown > RIR > Oh-Shamo > AUS > Onagadori > White Leghorn [33,34,35].…”
Section: Discussionmentioning
confidence: 99%